Analysis Geography of Energy with the Soar Method to Realize Sustainable Development Goals (SDGs) - Sulistya, Aryana Rachmad (Jurnal Pendidikan Geografi Gea, 2024)
Geography of Energy is the science of combining or collaborating two major scientific fields, namely geography and energy. The science of Geography of Energy emerged in the 19th century precisely in 1961, when geographers answered problems in the field of energy to encourage the fulfillment of energy needs, spatial distribution, supply patterns, and areas of energy production. The temporal spatial analysis of energy production, distribution, and use is referenced extensively in many studies around the world. This study examines : 1) description of the perspective of the field of Geography of Energy; 2) analysis of the role of Geography of Energy scientists in realizing SDGs point 7 with SOAR approach. The method used in this study is qualitative descriptive with SOAR approach. The conclusion of the study is that Geography of Energy is a science that is closely collaboration between the fields of Geography and Energy Science. Geography of Energy has a closeness between 4 sub fields, namely: (1) physical entities; (2) the main mediator of the environment-humans and / or society; (3) social relations; and (4) Geography of Energy Studies: the domain of GIScientist and cartography in the visualization (map). Geography of Energy has the potential to be developed because it forms a very clear mindset that is needed when analyzing, determining, predicting an energy resource in a region in order to realize the SDGs point 7 clean and affordable energy goals with information technology such as GISEnergy (Web-GIS based on energy data).